False colonic obstruction. - Bogliaccini, Gustavo; Perdomo, Roberto (Cirugía del Uruguay, 1977)
In this paper attention is drawn to a condition which can easily be mistaken for mechanic occlusion of colon, thus leading to mistaken medical and surgical therapy. Pathological and clinical caracteristics of false colonic obstructions are described, together with the condiÜons which have to be born in mind in order to establish- correct diagnosis